Designing for Digital Futures - Coombs, Emily; Manners, Arushi (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2024)
The global pandemic catalyzed a transformative shift in education, exposing the fragility and resilience of traditional systems as institutions rapidly pivoted to digital platforms. In Designing for Digital Futures, this editorial examines this abrupt transition's lessons, challenges, and opportunities. Drawing on insights from multiple contributors, it explores how integrating technology, including artificial intelligence, can reshape education while addressing persistent issues of equity, inclusion, and academic integrity. The editorial highlights various articles that delve into decision-making frameworks in faith-based and higher education institutions, the ethical dimensions of digital citizenship, and the evolving landscape of assessment and feedback practices. It also emphasizes the importance of centring Indigenous knowledge systems and decolonizing digital education. Through diverse perspectives, the edition invites reflection on how digital tools can enhance learning and foster more adaptive, inclusive, and human-centred educational environments. This collection challenges us to reimagine the future of education, where technology and tradition coexist to create equitable and dynamic learning ecosystems.